Assessing Microbial and Biochemical Quality Indicators of Tanos Treated Soils - Hawser Khurshid Mawlood; Nashmeel Saeed Khudhur (Zanco Journal of Pure and Applied Sciences, 2020)
Different doses of tanos fungicide and two soil textures in combination (2×4: soil texture × fungicide doses) were studied in a pot experiment under chickpea cultivation to determine their effects on certain soil chemical, biochemical and microbiological properties. The main results showed that: clayey soil showed highest pH, enzymatic activities and microbial population during this study. Tanos doses showed significant changes in soil EC, reduced urease (R² = 0.9775), dehydrogenase (R² = 0.8806) and nitrate reductase (R² = 0.8541) activities. Whereas, significant increases in bacterial and fungal population in response to tanos doses were observed after two months. According to paired t test results, different tanos doses, as well as the combination effects between soil textures and tanos doses have significantly changed fungal population, urease, dehydrogenase and nitrate reductase activities after two months of experiment. The combined treatment S2D3 showed the lowest nitrate reductase activity, bacterial and fungal counts during the study. A significant correlation (R² = 0.8581) was observed between urease activity and bacterial population.